2018
DOI: 10.1364/oe.26.018998
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of ordered hierarchical structures on stainless steel by picosecond laser for modified wettability applications

Abstract: Ordered hierarchical structures were fabricated on a stainless steel surface using a single picosecond laser for highly controllable dimensions. Picosecond laser induced periodic structures were firstly used to create large-scale nano-structures with a period of ~450 nm. Subsequently, laser direct writing, by simply changing process parameters was employed to create micro squared structures with 19 μm width, 19 μm interval and 3-7.5 μm depth on the previously created nano-structures. As a result, micro squared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…24: SEM images of spike surface generated by fs-laser processing in SF 6 atmosphere to mimic the Lotus leaf on low magnification (left) and high magnification (right) (Reproduced with permission from Zorba et al [164], and with permission from Wiley) in most of the cases SF 6 or in liquid environment [247,248]. The second approach is based on a twostep surface treatment [249,250] in which the laser beam is used to form an ablation pattern and in a second step the same beam with different parameters can decorate the unaffected regions with LIPSS.…”
Section: Hierarchical Structures and Complex Morphologiesmentioning
confidence: 99%
“…24: SEM images of spike surface generated by fs-laser processing in SF 6 atmosphere to mimic the Lotus leaf on low magnification (left) and high magnification (right) (Reproduced with permission from Zorba et al [164], and with permission from Wiley) in most of the cases SF 6 or in liquid environment [247,248]. The second approach is based on a twostep surface treatment [249,250] in which the laser beam is used to form an ablation pattern and in a second step the same beam with different parameters can decorate the unaffected regions with LIPSS.…”
Section: Hierarchical Structures and Complex Morphologiesmentioning
confidence: 99%
“…This limitation can be resolved by another laser texturing technique known as the direct laser interference patterning (DLIP), where multiple features can be created within a single spot. The second approach involves an initial creation of an ablation pattern using a laser beam and then applying different laser parameters to decorate the unaltered areas with laser-induced surface structures [46,47]. This approach is similar to laser-beam micromachining, with microfeatures fabricated on material surface by utilizing laser beam properties to achieve control and avoid any damage to surface integrity of the target material [30].…”
Section: Lst By Direct Writingmentioning
confidence: 99%
“…It was found that when the micro-and nanostructures were more complex and the ablation depth was deeper, more air could gather in the micro and nanostructure space, and the liquid could not completely wet the entire surface. In this case, the Cassie model and experimental results showed better agreement [55,56].…”
Section: Wetting Performancementioning
confidence: 58%
“…The surface roughness increased with an increasing laser fluence while the corresponding water contact angle was increased (maximum 142.5°) and ethylene glycol contact angle was decreased (minimum 6.4°). Xingsheng Wang et al [55] prepared an ordered hierarchical structures with highly controllable dimensions on a stainless steel surface using a picosecond laser in two steps, as shown in Figure 14. The first step was to prepare large-scale ripple structure of about 450 nm, while the second step used a laser direct-writing method to create a micro squared structure with a 19 µm width, 3~7.5 µm depth, and 19 µm interval.…”
Section: Wetting Performancementioning
confidence: 99%